2021
DOI: 10.24953/turkjped.2021.06.014
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between immature platelet fraction and severity of acute bronchiolitis

Abstract: Background and objectives. Acute bronchiolitis is one of the most common reasons for hospitalization in infants. Although patients with acute bronchiolitis generally have a good prognosis, death can also occur. In this study, we evaluate the immature platelet fraction (IPF) as an indicator of the severity of acute bronchiolitis.Methods. In our study, 179 patients diagnosed with acute bronchiolitis were divided into three groups as mild (n: 48; 26.8%), moderate (n: 104; 58.10%) and severe (n: 27; 15.1%) bronchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The WBC count will increase when there is infection and inflammatory reaction is intense, which is a defensive reaction of the body. Studies have shown that WBC counts can be used to predict and diagnose the severity of bronchiolitis ( 15 ). The rise of APTT indicates that the blood is in a hypercoagulable state, which is caused by the release of various inflammatory factors and clotting substances during infection ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…The WBC count will increase when there is infection and inflammatory reaction is intense, which is a defensive reaction of the body. Studies have shown that WBC counts can be used to predict and diagnose the severity of bronchiolitis ( 15 ). The rise of APTT indicates that the blood is in a hypercoagulable state, which is caused by the release of various inflammatory factors and clotting substances during infection ( 16 ).…”
Section: Discussionmentioning
confidence: 99%